PENGARUH MEDIA BONEKA TANGAN BERBASIS BERMAIN PERAN TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS IV SDN 09 RANTAU SELATAN - Hasibuan, Akhirunnisa; Arizka, Pilma Sindy; Ardiani, Shakila Khaira; P Wahyuni, Elly; Anshari, Khairil (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the effect of using role-play-based hand puppet media on the listening skills of fourth-grade students at SDN 09 Rantau Selatan. The research employed a quantitative experimental method with a one-group design. The population consisted of 25 fourth-grade students, who also served as the research sample. Data were collected using observation sheets. The results revealed a significant difference in students’ listening skills before and after the implementation of role-play-based hand puppet media. Before treatment, most students scored below the minimum mastery criteria (KKM), with the highest percentage (20%) in the 57–59 score range. After treatment, students’ scores increased significantly, ranging from 78 to 98, with the highest percentage (34%) in the 90–92 range. The paired sample t-test yielded a significance value of 0.000 (< 0.05) and a t-value of 17.744, indicating a significant effect of the use of role-play-based hand puppet media on students’ listening skills. The study concludes that role-play-based hand puppet media is effective in improving students’ listening skills, as it creates engaging, interactive, and enjoyable learning experiences that motivate students to focus and listen attentively.